THE THE POTENTIAL ROLE OF NRF2 AS A TARGET SITE FOR THERAPEUTIC INTERVENTIONS IN ALZHEIMER'S DISEASE - Rivarti, Arina Windri; Harahap, Herpan Syafii; Saputri, Legis Ocktaviana; Suryani, Dini; Rianawati, Sri Budhi (MNJ (Malang Neurology Journal), 2025)
Alzheimer's Disease (AD) is the most common form of dementia, characterized by progressive neurodegeneration leading to cognitive decline and memory impairment, affecting various cognitive functions. AD pathology involves the accumulation of neurotoxic substances such as amyloid beta (Aβ) and tau proteins, mitochondrial dysfunction, oxidative stress, and chronic neuroinflammation, resulting in synaptic loss and neuronal apoptosis. The transcription factor nuclear factor erythroid 2-related factor 2 (NRF2) has emerged as a pivotal regulator of cellular defense mechanisms, including antioxidant response, autophagy, and inflammation. NRF2 not only inhibits Aβ synthesis and enhances tau protein clearance via autophagy but also reduces neuroinflammation by modulating microglial activation and cytokine production. Additionally, NRF2 activation preserves mitochondrial function by attenuating reactive oxygen species (ROS) production and sustaining mitochondrial biogenesis. Recent studies highlight the therapeutic potential of NRF2 activators, such as sulforaphane and echinacoside, in preclinical AD models, demonstrating reductions in Aβ and tau pathologies and improved cognitive outcomes. These findings underscore the multifaceted role of NRF2 in mitigating AD progression and its promise as a target for developing novel therapeutic interventions. By integrating NRF2-based strategies, future treatments may offer more effective approaches to combat the complex pathophysiology of AD.